The Socioeconomic Determinants of Crime in Pakistan - Muhammad Umair (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
Crime is one of the major issues in Pakistan. It not only affects our society but also our economy. The main purpose of this study is showing the effects of socio-Economic factors such as Inflation, Population, income and economic growth to crimes. For this purpose we use secondary data and collected from Pakistan Bureau of Statistics and World Bank over 2006 to 2016. Correlation and regression analysis use to check the socio-economic effects on crimes. Results show negative relation of crime and economic growth. Government strives on economic growth, because it improves, crimes reduce gradually.